Fixed Point Theorems for Occasionally Weakly Compatible Maps in G-Metric Space - Manro, Saurabh (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper, we prove common fixed point theorems for a pair of occasionally weakly compatible maps in Symmetric G-metric space. Our results generalize and extend several relevant common fixed-point theorems from the literature.